American bison kill site use and abandonment amid drought and cultural shifts in late Holocene Montana - Wendt, John A. F.; Neeley, Michael; Alt, Mio; Ewing, Stephanie A.; Fischer, Georgianna S.; McWethy, David B. (Frontiers in Conservation Science, 2026)
Understanding how ecological and social constraints interacted to shape bison hunting systems during the late Holocene reveals the dynamic ways bison hunting strategies adapted to changing conditions. At the Bergstrom site in central Montana, bison were hunted intermittently for roughly seven centuries before archaeologically visible use ceased near 1100 cal yr BP. To explain why hunting stopped despite continued regional bison presence, we integrate archaeological excavation, radiocarbon chronology, and multiproxy riparian paleoecology (pollen, charcoal, coprophilous fungal spores) with regional drought reconstructions and analysis of radiocarbon-dated bison occurrences. Local environmental proxies show stable vegetation, low fire activity, and persistent large-herbivore indicators after abandonment, providing little support for ecological transformation as a cause. Regional synthesis reveals that archaeological bison frequencies increased 5.5-fold through the Holocene while paleontological frequencies remained stable, with peak hunting intensity coinciding with severe, multi-decadal droughts. These findings contradict models of population tracking and indicate that hunting reorganization, not prey scarcity, led to site abandonment. The most parsimonious explanation is convergence of constraints: drought reduced processing water at hydrologically marginal sites while rising organizational demands favored larger, infrastructure-intensive communal operations. The abandonment of the small Bergstrom site likely reflects an adaptive reorganization of bison hunting efforts toward larger, topographically advantageous sites better suited to increasingly coordinated communal hunting systems. This case study illustrates how historical hunting systems maintained regional persistence through episodic site use and localized abandonment, providing empirical guidance for contemporary managers seeking to restore the spatial heterogeneity and adaptive capacity that supported bison-human systems under climatic variability.